Treatment of Scabies in A Persian Mixed Cat at UPTD. Puskeswan, Bukittinggi City - Dwi Serly Septiana; Yurni Sari Amir; Sujatmiko Sujatmiko; Ramond Siregar; Engki Zelpina; Effi Silfia; Radhiati Kemala Sari (Universitas Airlangga, 2022)
Background: Sarcoptes scabiei is one of the ectoparasites that usually attack cats. This parasitic disease can be transmitted through direct contact with other animals affected by scabies or by the presence of a source of scabies in the area where the cat lives. Purposes: This study aimed to determine the handling of cases of scabies in a Persian mixed-breed cat (Pobo) at UPTD. Puskeswan, Bukittinggi City. Methods: Handling began with anamnesis and continued by examining the patient's physical condition and observing the body parts infected with scabies. A deep skin scraping was performed on the facial area, followed by microscopic and hematological examination. Results: Examination showed Sarcoptes scabiei infestation in the scraped skin layer and the cat was anemic. The cat patient with scabiosis received Ivomec® as an antiparasitic. Symptomatic treatment was also carried out by giving Vet-oxy SB® and Vetadryl® injections as antibiotics because a secondary infection was suspected. Conclusions: The therapy administered showed positive progressive results in the patient.